2015
DOI: 10.1016/j.ajhg.2015.07.007
|View full text |Cite
|
Sign up to set email alerts
|

Gain-of-Function Mutations in ZIC1 Are Associated with Coronal Craniosynostosis and Learning Disability

Abstract: Human ZIC1 (zinc finger protein of cerebellum 1), one of five homologs of the Drosophila pair-rule gene odd-paired, encodes a transcription factor previously implicated in vertebrate brain development. Heterozygous deletions of ZIC1 and its nearby paralog ZIC4 on chromosome 3q25.1 are associated with Dandy-Walker malformation of the cerebellum, and loss of the orthologous Zic1 gene in the mouse causes cerebellar hypoplasia and vertebral defects. We describe individuals from five families with heterozygous muta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
43
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 65 publications
(48 citation statements)
references
References 51 publications
2
43
0
Order By: Relevance
“…Coronal NCS (cNCS; incidence 1:10,000 live births) is thought to have a stonger genetic component compared to the other forms of NCS [Lajeunie et al, 1995; Wilkie et al, 2010] with specific monogenic mutations present in about 60% of patients with bicoronal and 30% of patients with unicoronal CS [Twigg et al, 2015c]. Indeed, diverse genes may account for the higher incidence of monogenic variants in cNCS.…”
Section: Genetic Etiopathogenesis Of Craniosynostosismentioning
confidence: 99%
See 3 more Smart Citations
“…Coronal NCS (cNCS; incidence 1:10,000 live births) is thought to have a stonger genetic component compared to the other forms of NCS [Lajeunie et al, 1995; Wilkie et al, 2010] with specific monogenic mutations present in about 60% of patients with bicoronal and 30% of patients with unicoronal CS [Twigg et al, 2015c]. Indeed, diverse genes may account for the higher incidence of monogenic variants in cNCS.…”
Section: Genetic Etiopathogenesis Of Craniosynostosismentioning
confidence: 99%
“…A heterozygous mutation in the last exon of ZIC1 was identified by exome sequencing in a proband with severe bicoronal CS, autism and developmental delay [Twigg et al, 2015c]. In order to clarify the significance of ZIC1 in the etiology of CS, the authors screened a cohort of 307 patients with various types of syndromic and nonsyndromic CS and identified 4 additional probands with bicoronal CS who had mutations in the last exon of ZIC1 .…”
Section: Genetic Etiopathogenesis Of Craniosynostosismentioning
confidence: 99%
See 2 more Smart Citations
“…ZIC1 is implicated in vertebrate brain development. The heterozygous loss of ZIC1 and ZIC4 has been suspected to lead to Dandy-Walker along with mental retardation, and mutations in ZIC1 were reported to be associated with learning disability [41,42]. From the analysis, it can be observed that gene regulatory networks provide rich information about how disease genes are regulated and may help predict new disease genes.…”
Section: Case Study: the Regulatory Network Of Intellectual Disabilitmentioning
confidence: 99%